2020
DOI: 10.1111/gcb.15353
|View full text |Cite
|
Sign up to set email alerts
|

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 76 publications
0
48
0
Order By: Relevance
“…From SRDB‐V5 we showed that approximately 85% of R S measurements do not measure 24 hr continuously, and likely many more of R S estimated from non‐continuous measurement will be reported in the future due to its low cost and portability. We thus suggest that linking SRDB‐V5 (strength at spatial coverage, Jian & Bond‐Lamberty, 2020) with COSORE (strength at temporal resolution, Bond‐Lamberty et al, 2020) in the future could provide an opportunity for better understanding global R S spatiotemporal variability.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…From SRDB‐V5 we showed that approximately 85% of R S measurements do not measure 24 hr continuously, and likely many more of R S estimated from non‐continuous measurement will be reported in the future due to its low cost and portability. We thus suggest that linking SRDB‐V5 (strength at spatial coverage, Jian & Bond‐Lamberty, 2020) with COSORE (strength at temporal resolution, Bond‐Lamberty et al, 2020) in the future could provide an opportunity for better understanding global R S spatiotemporal variability.…”
Section: Discussionmentioning
confidence: 93%
“…To test the effect of measurement frequency, a comparison of two methods at different sampling frequencies or resampling from continuous measurements can be used to test the effect of measurement frequency. Evaluating the effect of measurement duration and frequency in depth is outside the scope of this paper, but a new community database for continuous soil respiration (COSORE, Bond‐Lamberty et al, 2020) provides an opportunity to test it in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We begin with a detailed description of the Rs response to heatwaves at the San Joaquin Marsh Reserve (SJMR) site. We then extend our framework and analysis to ten other sites, from the continuous soil respiration database (COSORE v0.5) 36 , across the CONUS to better understand how different soils and climatic characteristics impact such findings. Using a conditional multivariate model, we tested the hypothesis that heatwaves significantly change Rs.…”
Section: Introductionmentioning
confidence: 99%
“…This dynamic physiological regulation of leaf respiration calls into question the validity of estimating daytime R eco from night-time measurements (Keenan et al, 2019;Wehr et al, 2016). R soil has been measured continuously at an increasing number of sites (Bond-Lamberty et al, 2020) and can provide a check of consistency for eddy-covariance based R eco estimates, because R eco = R soil + R AG . This constraint indicates that R eco should be larger in absolute magnitude compared to R soil , and the difference in temporal dynamic between R eco and R soil should be a result of the R AG temporal dynamic (Barba et al, 2018;Phillips et al, 2017;Wang et al, 2017).…”
mentioning
confidence: 99%